Peles de vidro: otimização do desempenho da luz natural difusa em fachadas envidraçadas - Risso, Erika Ciconelli de Figueiredo (2016)
The consumption of energy by artificial lighting and air-conditioning systems is the most costly element of building maintenance. Analyses of energy consumption indicate that, although systems are becoming more efficient, in the long term, energy production will not be able to keep up with demand, indicating the need to improve our use of natural resources. The viable use of daylight in office interiors is subject to certain factors, such as glass light transmission, ceiling height, building shape and dimension, the quantity and size of openings, sky model, and the use of solar protections, among others. This study examines the performance of diffuse daylight as the result of the glass facade, solar protection, and light shelves utilized in Towers A and B of the Rochaverá Corporate Towers, in São Paulo, SP, Brazil, through static and dynamic simulations in the programs ReluxPro and Daysim. The study was divided into two parts; the first part involved the acquisition of meteorological data from databases maintained by the Institute of Astronomy, Geophysics and Atmospheric Sciences, IAG. Global solar radiation data was entered into Liu and Jordan’s mathematical model in order to determine the frequency of three basic sky models: clear sky, intermediate sky and overcast sky. The second part of the study assessed the actual performance of the systems in Towers A and B, as well as the projected performance of the proposed systems for both towers. The combination of types of glazing, solar protection and light shelves reduces the incidence of direct sunlight in office interiors and widens the distribution of diffuse daylight. Through this examination it was possible to outline parameters that could influence design decisions.